Glass, glass-ceramics and chemically strengthened glass
By adjusting the composition of the glass and adopting chemical reinforcement treatment, the lack of alkali-free glass in strength and radio wave transmission is solved, and high-strength and excellent transmission glass is achieved, which is suitable for high-frequency communication systems.
Patent Information
- Application Number
- CN202180047080.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-03
- Filing Date
- 2021-07-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-07-02
AI Technical Summary
It is difficult for existing alkali-free glasses to take into account high strength and excellent radio wave transmission, and the relative dielectric constant and dielectric loss tangent of existing chemically reinforced glasses in high-frequency regions have not been paid enough attention.
By adjusting the glass composition, a glass containing a specific mole percent range of oxides is prepared, chemically strengthened to improve strength, and by optimizing the glass composition to improve radio wave transmission.
It realizes high-strength glass obtained through chemical reinforcement, and has excellent radio wave transmission, and is suitable for portable terminals of high-frequency communication systems.
Smart Images

Figure CN115734948B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to glass, glass-ceramics and chemically strengthened glass. Background Art
[0002] For the protective glass of portable terminals, etc., chemically strengthened glass is widely used because it is required to have a strength that is not easy to break even if the portable terminal falls from a height. Chemically strengthened glass is a glass formed with a compressive stress layer on the surface of the glass by immersing the glass in a molten salt such as sodium nitrate, so that the alkali ions contained in the glass are exchanged with the alkali ions with a larger ion radius contained in the molten salt. For example, Patent Document 1 discloses an aluminosilicate glass having a specific composition and having a high surface compressive stress obtained by chemical strengthening. In addition, Patent Document 2 discloses a glass article containing SiO2, Al2O3, B2O3, Li2O, SnO2 and having a fusion line, and records that such a glass article can be strengthened by an ion exchange process.
[0003] On the other hand, in electronic devices such as mobile phones, smart phones, portable information terminals, Wi-Fi devices, etc., surface acoustic wave (SAW) devices, radar components, antenna components, etc., in order to achieve large communication capacity and high communication speed, the high frequency of signal frequencies is developing. In recent years, as a new communication system using a higher frequency band, 5G (fifth-generation mobile communication system) is expected to become popular. In the high frequency band used in 5G, protective glass sometimes hinders the transmission and reception of radio waves. For portable terminals that cope with 5G, protective glass with excellent radio wave transmittance is required.
[0004] As glass with high radio wave transmittance in high frequency bands, such as that used in 5G, that is, glass with small relative dielectric constant and dielectric loss tangent, several types of alkali-free glass have been developed so far (for example, Patent Document 3).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2018-520082
[0008] Patent Document 2: Japanese Patent Application No. 2019-532906
[0009] Patent Document 3: International Publication No. 2019 / 181707 Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, alkali-free glass containing almost no alkali ions is difficult to chemically strengthen, and it is difficult to take into account both radio wave transmittance and strength. In addition, in the previous chemically strengthened glass as described in Patent Documents 1 and 2, no special attention is paid to the relative dielectric constant and dielectric loss tangent in the high-frequency region. Even if the strength is sufficient, it cannot be said that the radio wave transmittance is sufficient. Therefore, the object of the present invention is to provide a glass that can obtain excellent strength and excellent radio wave transmittance by chemical strengthening. In addition, the object of the present invention is to provide a chemically strengthened glass with excellent strength and excellent radio wave transmittance.
[0012] Means used to solve problems
[0013] The present inventors have found through research that by adjusting the glass composition, it is possible to obtain a glass that can obtain high strength through chemical strengthening and has good radio wave transmittance, thereby completing the present invention.
[0014] That is, the present invention is a glass comprising, in terms of molar percentage based on oxides:
[0015] 50.0%~75.0% SiO2,
[0016] 7.5% to 25.0% Al2O3,
[0017] 0~25.0% B2O3,
[0018] 6.5% to 20.0% Li2O,
[0019] 1.5% to 10.0% Na2O,
[0020] 0~4.0% K2O,
[0021] 1.0% to 20.0% MgO,
[0022] 1.0% to 20.0% in total of one or more selected from MgO, CaO, SrO, BaO, and
[0023] 0~5.0% TiO2, and
[0024] The value of Y calculated based on the following formula using the molar percentage of each component of MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O on an oxide basis: [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], [K2O], is less than 19.5.
[0025] Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O]).
[0026] Regarding the glass of the present invention, the value of X calculated based on the following formula using the contents of each component Al2O3, MgO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [Al2O3], [MgO], [Li2O], [Na2O], and [K2O] is preferably greater than 30.0.
[0027] X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O]).
[0028] The present invention is a glass, wherein, in terms of molar percentage based on oxides, the glass contains:
[0029] 55.0%~75.0% SiO2,
[0030] 9.1%~25.0% Al2O3,
[0031] 0~14.0% B2O3,
[0032] 7.5% to 12.5% Li2O,
[0033] 3.6% to 10.0% Na2O,
[0034] 0~2.0% K2O,
[0035] A total of 0 to 13.0% of at least one selected from MgO, CaO, SrO, and BaO, and 0 to 8.0% of ZnO, and
[0036] Using the contents of each component Al2O3, B2O3, MgO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [Al2O3], [B2O3], [MgO], [Li2O], [Na2O], [K2O], the value of X calculated based on the following formula is greater than 25.0, and the value of Z is less than 22.0.
[0037] X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O])
[0038] Z=3×[Al2O3]-3×[B2O3]-2×[Li2O]+4×[Na2O].
[0039] The present invention is a glass, wherein, in terms of molar percentage based on oxides, the glass contains:
[0040] 50.0%~75.0% SiO2,
[0041] 9.0%~25.0% Al2O3,
[0042] 0~20.0% B2O3,
[0043] 6.5% to 14.5% Li2O,
[0044] 2.5% to 10.0% Na2O,
[0045] 0~4.0% K2O,
[0046] A total of 0 to 20.0% of at least one selected from MgO, CaO, SrO, BaO, and 0 to 3.0% of TiO2, and
[0047] Using the contents of each component Al2O3, B2O3, MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [Al2O3], [B2O3], [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], [K2O], the value of X calculated based on the following formula is greater than 35.0, and the total value of the value of Y and the value of Z is less than 35.0.
[0048] X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O])
[0049] Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O])
[0050] Z=3×[Al2O3]-3×[B2O3]-2×[Li2O]+4×[Na2O]
[0051] The plate thickness (t) of the glass of the present invention is preferably 100 μm or more and 2000 μm or less.
[0052] The present invention relates to a chemically strengthened glass, wherein the basic composition of the chemically strengthened glass comprises, in terms of molar percentage based on oxides:
[0053] 50.0%~75.0% SiO2,
[0054] 0~25.0% B2O3,
[0055] 7.5% to 25.0% Al2O3,
[0056] 6.5% to 20.0% Li2O,
[0057] 1.5% to 10.0% Na2O,
[0058] 0~4.0% K2O,
[0059] 1.0% to 20.0% MgO,
[0060] 1.0% to 20.0% in total of one or more selected from MgO, CaO, SrO, BaO, and
[0061] 0~5.0% TiO2, and
[0062] The value of Y calculated based on the following formula using the molar percentage of each component of MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O on an oxide basis: [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], [K2O], is less than 19.5.
[0063] Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O])
[0064] The surface compressive stress value CS0 of the chemically strengthened glass of the present invention is preferably 300 MPa or more.
[0065] The compressive stress value CS at a depth of 50 μm from the glass surface of the chemically strengthened glass of the present invention is 50 It is preferably 75 MPa or more, and the thickness (t) of the chemically strengthened glass is preferably 300 μm or more.
[0066] The compressive stress layer depth DOL of the chemically strengthened glass of the present invention is preferably 80 μm or more, and the plate thickness (t) of the chemically strengthened glass is preferably 350 μm or more.
[0067] The present invention relates to glass-ceramics having the glass composition of the glass of the present invention described above.
[0068] Effects of the Invention
[0069] The glass of the present invention has a glass composition within a specific range, and thus can obtain high strength by chemical strengthening, and exhibits excellent radio wave transmittance. In addition, the chemically strengthened glass of the present invention exhibits excellent strength and radio wave transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1This is a graph showing the relationship between the parameter X in the examples of the present glass and the surface compressive stress value CS0(Na) when the present glass is chemically strengthened.
[0071] Figure 2 This is a graph showing the relationship between the parameter Y and the relative dielectric constant at 10 GHz in Examples of the present glass.
[0072] Figure 3 This is a graph showing the relationship between the parameter Z and the dielectric loss tangent tanδ at 10 GHz in Examples of the present glass. DETAILED DESCRIPTION
[0073] In this specification, "to" indicating a numerical range is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit. Unless otherwise specified, "to" is used in the same meaning in this specification.
[0074] In this specification, "chemically strengthened glass" refers to glass subjected to a chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before subjected to a chemical strengthening treatment.
[0075] In this specification, "basic composition of chemically strengthened glass" refers to the glass composition of chemically strengthened glass. In chemically strengthened glass, the glass composition at a depth of 1 / 2 of the plate thickness t is the basic composition of chemically strengthened glass, except for the case of extreme ion exchange treatment.
[0076] In this specification, unless otherwise specified, the glass composition is expressed as a molar percentage based on oxides, and mol % is simply expressed as "%".
[0077] In this specification, “substantially free of” means that the content is lower than the impurity level contained in the raw materials, that is, it is not intentionally contained. Specifically, “substantially free of” means that the content is less than 0.1 mol %, for example.
[0078] In this specification, "stress distribution" refers to a graph that expresses the compressive stress value with the depth from the glass surface as a variable. In addition, "compressive stress layer depth (DOL)" is the depth at which the compressive stress value (CS) is zero. "Internal tensile stress value (CT)" refers to the tensile stress value at a depth of 1 / 2 of the glass plate thickness t.
[0079] The stress distribution in this specification can be measured using a scattered light photoelastic stress meter (for example, SLP-1000 manufactured by Orihara Seisakusho Co., Ltd.). The scattered light photoelastic stress meter is affected by surface scattering, and sometimes the measurement accuracy near the sample surface is reduced. However, for example, in the case where compressive stress is generated only by ion exchange between lithium ions in the glass and external sodium ions, since the compressive stress value expressed as a function of depth follows the complementary error function, the surface stress value can be known by measuring the internal stress value. In the case where the compressive stress value expressed as a function of depth does not follow the complementary error function, the surface portion is measured by other methods, such as a method of measurement using a surface stress meter.
[0080] <Glass>
[0081] The glass of the embodiment of the present invention (hereinafter sometimes referred to as the present glass) is preferably lithium aluminosilicate glass. Since lithium aluminosilicate glass contains lithium ions, which are alkaline ions with the smallest ionic radius, chemically strengthened glass having a preferred stress distribution and excellent strength can be easily obtained by chemical strengthening treatment using various molten salts for ion exchange.
[0082] Specifically, the present glass preferably contains:
[0083] 50.0%~75.0% SiO2,
[0084] 7.5% to 25.0% Al2O3, and
[0085] 6.5% to 20.0% Li2O.
[0086] In addition, the glass preferably further contains:
[0087] 0~25.0% B2O3,
[0088] 1.5% to 10.0% Na2O,
[0089] 0~4.0% K2O, and
[0090] A total of 0 to 20.0% of one or more selected from MgO, CaO, SrO, and BaO.
[0091] In the present glass, the value of parameter X calculated based on the following formula using the contents [Al2O3], [MgO], [Li2O], [Na2O], [K2O] of each component Al2O3, MgO, Li2O, Na2O, and K2O in terms of oxide-based molar percentage is preferably 25.0 or more. The value of parameter X is more preferably 30.0 or more, further preferably 35.0 or more, further preferably 37.5 or more, particularly preferably 40.0 or more, further preferably 42.0 or more, and most preferably 45.0 or more.
[0092] X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O])
[0093] Figure 1 This is a graph showing the relationship between the value of parameter X in the embodiment of the present glass and the surface compressive stress value CS0(Na) when the present glass is chemically strengthened. It should be noted that the surface compressive stress value CS0(Na) here refers to the surface compressive stress value when the glass is chemically strengthened by immersing it in 100% sodium nitrate salt at 450°C for 1 hour. Figure 1 It can be confirmed that the larger the value of parameter X is, the larger the CS0(Na) is. Specifically, by setting the value of parameter X to 25.0 or more, it is easy to obtain a chemically strengthened glass having excellent strength by chemical strengthening. From the viewpoint of the strengthening time of the glass, the value of parameter X is preferably 80.0 or less, more preferably 55.0 or less, further preferably 50.0 or less, further preferably 49.0 or less, particularly preferably 48.0 or less, further preferably 47.0 or less, and most preferably 46.0 or less.
[0094] In the present glass, the value of parameter Y calculated based on the following formula using the contents [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], [K2O] of each component as molar percentage on an oxide basis of MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O is preferably 19.5 or less. The value of parameter Y is more preferably 19.0 or less, further preferably 18.5 or less, still further preferably 18.25 or less, particularly preferably 18.0 or less, further preferably 17.5 or less, and most preferably 17.0 or less.
[0095] In addition, when a large amount of B2O3 is contained, from the viewpoint of suppressing the phase separation of the glass, it is preferred to reduce the components that increase the value of Y. Specifically, when B2O3 is greater than 5.0%, the value of Y is preferably 18.0 or less, more preferably 17.75 or less, further preferably 17.5 or less, further preferably 17.25 or less, particularly preferably 17.0 or less, further preferably 16.75 or less, and most preferably 16.5 or less.
[0096] Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O])
[0097] Figure 2 Graph showing the relationship between the value of parameter Y and the relative dielectric constant at 10 GHz in the examples of the present glass. Figure 2 It can be confirmed that the smaller the value of parameter Y is, the smaller the relative dielectric constant at 10GHz is. That is, specifically, by making the value of parameter Y less than 19.5, it is easy to obtain a glass with a smaller relative dielectric constant and good radio wave transmittance. From the viewpoint of making the glass high-strength, the value of parameter Y is preferably 10.0 or more, more preferably 11.0 or more, more preferably 12.0 or more, more preferably 13.0 or more, particularly preferably 14.0 or more, more preferably 15.0 or more, and most preferably 15.5 or more.
[0098] Regarding the present glass, the value of parameter Z calculated based on the following formula using the contents of each component Al2O3, B2O3, Li2O, and Na2O in terms of molar percentage on an oxide basis [Al2O3], [B2O3], [Li2O], and [Na2O] is preferably 22.0 or less, more preferably 21.0 or less, further preferably 20.0 or less, further preferably 19.0 or less, particularly preferably 18.0 or less, further preferably 14.0 or less, and most preferably 12.0 or less.
[0099] Z=3×[Al2O3]-3×[B2O3]-2×[Li2O]+4×[Na2O]
[0100] Figure 3It is a graph showing the relationship between the value of parameter Z in the embodiment of the present glass and the dielectric loss tangent tanδ at 10GHz. It can be confirmed that the smaller the value of parameter Z, the smaller the tanδ at 10GHz. That is, specifically, by making the value of parameter Z less than 22.0, it is easy to obtain a glass with a smaller dielectric loss tangent and good radio wave transmittance. From the viewpoint of obtaining high-strength glass during chemical strengthening, the value of parameter Z is preferably greater than -5.0, more preferably greater than 0.0, further preferably greater than 2.0, further preferably greater than 4.0, particularly preferably greater than 6.0, further preferably greater than 8.0, and most preferably greater than 10.0.
[0101] The total value of the parameter Y value and the parameter Z value of the present glass is preferably 35.0 or less, more preferably 33.0 or less, further preferably 32.0 or less, further preferably 31.0 or less, particularly preferably 30.0 or less, further preferably 29.0 or less, and most preferably 28.0 or less. In addition, in the case of containing a large amount of B2O3, from the viewpoint of suppressing the phase separation of the glass, it is preferred to reduce the components that increase the values of Y and Z. Specifically, in the case of B2O3 being greater than 5.0%, the value of Y+Z is preferably 34.0 or less, more preferably 32.0 or less, further preferably 30.0 or less, further preferably 28.0 or less, particularly preferably 27.0 or less, further preferably 26.0 or less, and most preferably 25.5 or less.
[0102] By making the total value of the value of Y and the value of Z 35.0 or less, it is easy to obtain a glass with both smaller relative dielectric constant and dielectric loss tangent and good radio wave transmittance. From the viewpoint of making the glass high-strength, the total value of the value of Y and the value of Z is preferably 0.0 or more, more preferably 10.0 or more, further preferably 15.0 or more, further preferably 20.0 or more, particularly preferably 21.0 or more, further preferably 23.0 or more, and most preferably 25.0 or more.
[0103] Hereinafter, a preferred composition of the present glass will be further described.
[0104] SiO2 is a component constituting a network of glass. In addition, SiO2 is a component that improves chemical durability and is a component that reduces cracks generated when damage occurs on the glass surface.
[0105] In order to improve chemical durability, the content of SiO2 is preferably 50.0% or more, more preferably 52.0% or more, further preferably 55.0% or more, further preferably 56.0% or more, particularly preferably 60.0% or more, further particularly preferably 62.0% or more, further preferably 64.0% or more, and most preferably 66.0 or more. On the other hand, in order to improve the meltability during glass manufacturing, the content of SiO2 is preferably 75.0% or less, more preferably 74.0% or less, further preferably 72.0% or less, further preferably 71.0% or less, particularly preferably 70.0% or less, further preferably 69.0% or less, and most preferably 68.0% or less.
[0106] Al2O3 is an effective component from the viewpoint of improving the ion exchange performance during chemical strengthening and increasing the surface compressive stress after strengthening.
[0107] In order to improve chemical durability or improve chemical strengthening characteristics, the content of Al2O3 is preferably 7.5% or more, more preferably 9.0% or more, further preferably 9.1% or more, further preferably 9.5% or more, particularly preferably 10.0% or more, further preferably 11.0% or more, and most preferably 12.0% or more. On the other hand, when the content of Al2O3 is too much, crystals sometimes grow easily in the melt. In order to prevent the reduction of yield caused by devitrification defects, the content of Al2O3 is preferably 25.0% or less, more preferably 23.0% or less, further preferably 21.0% or less, further preferably 20.0% or less, particularly preferably 16.0% or less, further preferably 15.0% or less, and most preferably 13.5% or less.
[0108] Both SiO2 and Al2O3 are components that stabilize the glass structure. In order to reduce brittleness, the combined content of SiO2 and Al2O3 is preferably 57.5% or more, more preferably 65.0% or more, further preferably 75.0% or more, further preferably 77.0% or more, and particularly preferably 79.0% or more.
[0109] SiO2 and Al2O3 both have a tendency to increase the melting temperature of glass. Therefore, in order to make the glass melt easily, the total content is preferably 95.0% or less, more preferably 90.0% or less, further preferably 87.0% or less, further preferably 85.0% or less, and particularly preferably 82.0% or less.
[0110] Li2O is a component that forms surface compressive stress through ion exchange and is a component that improves the solubility of glass. By making chemically strengthened glass contain Li2O, by exchanging Li ions on the surface of the glass with Na ions and further exchanging Na ions with K ions, a stress distribution with large surface compressive stress and compressive stress layer can be obtained.
[0111] In order to increase the surface compressive stress during chemical strengthening, the Li2O content is preferably 6.5% or more, more preferably 7.1% or more, further preferably 7.5% or more, further preferably 7.6% or more, particularly preferably 8.0% or more, further particularly preferably 8.1% or more, further preferably 8.5% or more, and most preferably 9.0% or more.
[0112] On the other hand, when the content of Li2O is too much, the crystal growth rate during glass molding increases, and the problem of reduced yield caused by devitrification defects sometimes becomes larger. In order to suppress devitrification in the glass manufacturing process, the content of Li2O is preferably 20.0% or less, more preferably 18.0% or less, further preferably 16.0% or less, further preferably 14.5% or less, particularly preferably 14.0% or less, further particularly preferably 12.5% or less, further preferably 12.0% or less, and most preferably 11.0% or less. In addition, when the content of alkali ions is too much, radio wave transmittance tends to decrease, so from the perspective of making radio wave transmittance good, the content of Li2O is preferably 12.0% or less, more preferably 11.0% or less, further preferably 10.0% or less, and further preferably 9.5% or less.
[0113] Although both Na2O and K2O are not essential, Na2O and K2O are components that improve the solubility of glass and reduce the crystal growth rate of glass. In order to improve the ion exchange performance, Na2O and K2O are preferably contained.
[0114] Na2O is a component that forms a surface compressive stress layer in a chemical strengthening treatment using potassium salt, and is a component that can improve the solubility of glass. In order to obtain this effect, the content of Na2O is preferably 1.5% or more, more preferably 2.5% or more, further preferably 3.0% or more, further preferably 3.3% or more, particularly preferably 3.5% or more, further preferably 3.6% or more, and most preferably 4.0% or more. On the other hand, when the content of Na2O is too much, it is difficult to increase the compressive stress of the portion deeper from the surface by chemical strengthening. Therefore, from this point of view, the content of Na2O is preferably 10.0% or less, more preferably 9.0% or less, further preferably 8.0% or less, further preferably 7.0% or less, particularly preferably 6.0% or less, further preferably 5.5% or less, and most preferably 5.0% or less.
[0115] In order to suppress devitrification in the glass manufacturing process, K2O may be contained. When K2O is contained, the content of K2O is preferably 0.1% or more, more preferably 0.15% or more, further preferably 0.2% or more, further preferably 0.25% or more, particularly preferably 0.3% or more, and further preferably 0.4% or more. In addition, in order to further prevent devitrification, the content of K2O is preferably 0.45% or more, more preferably 0.6% or more, further preferably 0.7% or more, further preferably 0.8% or more, particularly preferably 0.9% or more, and further preferably 1.0% or more. On the other hand, from the viewpoint of suppressing the increase of brittleness and suppressing the reduction of surface stress caused by reverse exchange during strengthening, the content of K2O is preferably 4.0% or less, more preferably 3.5% or less, further preferably 3.0% or less, further preferably 2.5% or less, particularly preferably 2.0% or less, further preferably 1.5% or less, further preferably 1.3% or less, and most preferably 1.1% or less.
[0116] In order to improve the solubility of glass, the total content of Na2O and K2O ([Na2O] + [K2O]) is preferably 1.0% or more, more preferably 2.0% or more, further preferably 3.0% or more, further preferably 4.0% or more, particularly preferably 5.0% or more, further preferably 5.5% or more, and most preferably 6.0% or more. When ([Na2O] + [K2O]) is too much, the surface compressive stress value is likely to decrease, so ([Na2O] + [K2O]) is preferably 18.0% or less, more preferably 16.0% or less, further preferably 15.0% or less, further preferably 14.0% or less, particularly preferably 12.0% or less, further preferably 10.0% or less, and most preferably 8.0% or less.
[0117] In addition, by making Na2O and K2O coexist, the migration of alkali components can be suppressed, which is preferable from the viewpoint of radio wave transmittance.
[0118] MgO, CaO, SrO, and BaO are not essential, but from the perspective of improving the stability of the glass and the perspective of improving the chemical strengthening characteristics, any one or more of them may be contained. When these substances are contained, the total content of one or more selected from MgO, CaO, SrO, and BaO [MgO] + [CaO] + [SrO] + [BaO] is preferably 1.0% or more, more preferably 1.5% or more, further preferably 2.0% or more, further preferably 2.5% or more, particularly preferably 3.0% or more, further preferably 3.5% or more, and most preferably 5.0% or more. In addition, from the perspective of introducing sufficient chemical strengthening stress during chemical strengthening and improving radio wave transmittance, the total content of these is preferably 20.0% or less, more preferably 16.0% or less, further preferably 15.0% or less, further preferably 14.0% or less, particularly preferably 13.0% or less, further particularly preferably 12.0% or less, further preferably 10.0% or less, and most preferably 8.0% or less.
[0119] MgO may be contained in order to reduce the viscosity during melting, etc. When MgO is contained, the content of MgO is preferably 1.0% or more, more preferably 1.5% or more, further preferably 2.0% or more, further preferably 2.5% or more, particularly preferably 3.0% or more, further preferably 3.5% or more, and most preferably 5.0% or more. On the other hand, when the content of MgO is too much, it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of MgO is preferably 20.0% or less, more preferably 16.0% or less, further preferably 15.0% or less, further preferably 14.0% or less, particularly preferably 12.0% or less, further preferably 10.0% or less, and most preferably 8.0% or less.
[0120] CaO is a component that improves the meltability of glass, and CaO may be contained. When CaO is contained, the content of CaO is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. On the other hand, when the content of CaO is excessive, it is difficult to increase the compressive stress value during chemical strengthening treatment. From such a viewpoint, the content of CaO is preferably 5.0% or less, more preferably 4.0% or less, further preferably 3.0% or less, and typically 1.0% or less.
[0121] Although ZnO is not essential, it is a component that improves the meltability of the glass and may be contained. When ZnO is contained, the content of ZnO is preferably 0.2% or more, more preferably 0.5% or more. In order to improve the weather resistance of the glass, the content of ZnO is preferably 8.0% or less, more preferably 5.0% or less, and further preferably 3.0% or less.
[0122] Since ZnO, SrO and BaO tend to deteriorate chemical strengthening properties, the total content of [ZnO]+[SrO]+[BaO] is preferably less than 1.0%, more preferably 0.5% or less, in order to facilitate chemical strengthening. It is further preferred that ZnO, SrO and BaO are substantially not contained.
[0123] ZrO2 may not be contained, but from the viewpoint of increasing the surface compressive stress of chemically strengthened glass, it is preferably contained. The content of ZrO2 is preferably 0.1% or more, more preferably 0.15% or more, further preferably 0.2% or more, particularly preferably 0.25% or more, and typically 0.3% or more. On the other hand, when the content of ZrO2 is too high, devitrification defects are likely to occur, and it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of ZrO2 is preferably 2.0% or less, more preferably 1.5% or less, further preferably 1.0% or less, and particularly preferably 0.8% or less.
[0124] Y2O3 is not essential, but in order to increase the surface compressive stress of chemically strengthened glass while reducing the crystal growth rate, it is preferably contained. In addition, in order to increase the fracture toughness value, it is preferred to contain a total of 0.2% or more of any one of Y2O3, La2O3 and ZrO2. The total content of Y2O3, La2O3 and ZrO2 is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.5% or more. In addition, in order to lower the liquidus temperature and suppress devitrification, their total content is preferably 6.0% or less, more preferably 5.0% or less, and further preferably 4.0% or less.
[0125] In order to lower the devitrification temperature and inhibit devitrification, the total content of Y2O3 and La2O3 is preferably greater than the content of ZrO2, and the content of Y2O3 is more preferably greater than the content of ZrO2.
[0126] The content of Y2O3 is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 1.0% or more. On the other hand, when the content of Y2O3 is too much, it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of Y2O3 is preferably 10.0% or less, more preferably 8.0% or less, further preferably 5.0% or less, further preferably 3.0% or less, particularly preferably 2.0% or less, and further particularly preferably 1.5% or less.
[0127] Although La2O3 is not essential, it may be contained for the same reason as Y2O3. La2O3 is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 0.8% or more. On the other hand, when La2O3 is too much, it is difficult to increase the compressive stress value during chemical strengthening treatment, so it is preferably 5.0% or less, more preferably 3.0% or less, further preferably 2.0% or less, and particularly preferably 1.5% or less.
[0128] Although TiO2 is not essential, it is a component that inhibits the solarization of glass, and TiO2 may be contained. When TiO2 is contained, the content of TiO2 is preferably 0.02% or more, more preferably 0.03% or more, further preferably 0.04% or more, particularly preferably 0.05% or more, and typically 0.06% or more. On the other hand, when the content of TiO2 is greater than 5.0%, devitrification is likely to occur, and the quality of chemically strengthened glass may be reduced. The content of TiO2 is preferably 5.0% or less, more preferably 3.0% or less, further preferably 2.0% or less, further preferably 1.0% or less, particularly preferably 0.5% or less, and further particularly preferably 0.25% or less.
[0129] B2O3 is not essential, but B2O3 may be contained for the purpose of reducing the brittleness of the glass, improving crack resistance, and also for the purpose of improving radio wave transmittance. When B2O3 is contained, the content of B2O3 is preferably 2.0% or more, more preferably 3.0% or more, further preferably 4.0% or more, further preferably 5.0% or more, particularly preferably 6.0% or more, further preferably 7.0% or more, and most preferably 8.0% or more. On the other hand, when the content of B2O3 is too much, the acid resistance tends to deteriorate, so the content of B2O3 is preferably 25.0% or less. The content of B2O3 is more preferably 20.0% or less, further preferably 17.0% or less, further preferably 14.0% or less, particularly preferably 12.0% or less, further preferably 10.0% or less, and most preferably 9.0% or less.
[0130] P2O5 is not essential, but may be contained for the purpose of increasing the compressive stress layer during chemical strengthening. When P2O5 is contained, the content of P2O5 is preferably 0.5% or more, more preferably 1.0% or more, further preferably 2.0% or more, further preferably 2.5% or more, particularly preferably 3.0% or more, further preferably 3.5% or more, and most preferably 4.0% or more. On the other hand, from the viewpoint of improving acid resistance, the content of P2O5 is preferably 10.0% or less, more preferably 9.0% or less, further preferably 8.0% or less, further preferably 7.0% or less, particularly preferably 6.0% or less, and further preferably 5.0% or less.
[0131] The total content of B2O3 and P2O5 is preferably 0 to 35.0%, preferably 3.0% or more, more preferably 5.0% or more, further preferably 7.0% or more, further preferably 9.0% or more, particularly preferably 11.0% or more, further preferably 13.0% or more, and most preferably 15.0% or more. The total content of B2O3 and P2O5 is preferably 35.0% or less, more preferably 25.0% or less, further preferably 23.0% or less, further preferably 21.0% or less, particularly preferably 20.0% or less, further particularly preferably 19.0% or less, and most preferably 18.0% or less.
[0132] Nb2O5, Ta2O5, Gd2O3, and CeO2 are components that inhibit the sunlight of glass and improve the solubility. Nb2O5, Ta2O5, Gd2O3, and CeO2 may be contained. When these components are contained, their total content is preferably 0.03% or more, more preferably 0.1% or more, further preferably 0.3% or more, and typically 0.5% or more. On the other hand, when their content is too much, it is difficult to increase the compressive stress value during chemical strengthening treatment. From this point of view, the total content of these components is preferably 3.0% or less, more preferably 2.0% or less, and particularly preferably 1.0% or less.
[0133] Fe2O3 absorbs heat rays, so it has the effect of improving the solubility of glass. When a large melting furnace is used to mass produce glass, it is preferable to contain Fe2O3. In this case, the content of Fe2O3 is preferably 0.002% or more, more preferably 0.005% or more, further preferably 0.007% or more, and particularly preferably 0.01% or more, based on the weight % of the oxide. On the other hand, when Fe2O3 is contained in excess, coloring occurs. Therefore, from the viewpoint of improving the transparency of the glass, its content is preferably 0.3% or less, more preferably 0.04% or less, further preferably 0.025% or less, and particularly preferably 0.015% or less, based on the weight % of the oxide.
[0134] It should be noted that all iron oxides in the glass are described here in the form of Fe2O3, but in reality, oxidized Fe(III) and reduced Fe(II) are usually present in a mixture. Among them, Fe(III) produces yellow coloration, Fe(II) produces blue coloration, and the glass produces green coloration under the balance of the two.
[0135] In addition, coloring components can be added within a range that does not hinder the desired chemical strengthening characteristics. As coloring components, for example, Co3O4, MnO2, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, CeO2, Er2O3, Nd2O3, etc. can be listed as appropriate components.
[0136] The content of the coloring components is preferably 5.0% or less in total in terms of molar percentage based on oxides. When it is greater than 5.0%, the glass may be easily devitrified. The content of the coloring components is preferably 3.0% or less, more preferably 1.0% or less. In the case of increasing the transmittance of the glass, it is preferred that these components are substantially absent.
[0137] As a clarifier for melting glass, SO3, chloride, fluoride, etc. may be appropriately contained. Preferably, As2O3 is not contained. When Sb2O3 is contained, the content of Sb2O3 is preferably 0.3% or less, more preferably 0.1% or less, and most preferably, no Sb2O3 is contained.
[0138] Specific examples of preferred compositions of the present glass are not limited, and for example, the following Composition Examples 1 to 4 can be cited.
[0139] (Composition Example 1)
[0140] A glass comprising:
[0141] 50.0%~75.0% SiO2,
[0142] 7.5% to 25.0% Al2O3,
[0143] 0~25.0% B2O3,
[0144] 6.5% to 20.0% Li2O,
[0145] 1.5% to 10.0% Na2O,
[0146] 0~4.0% K2O,
[0147] 1.0% to 20.0% MgO,
[0148] 1.0% to 20.0% in total of one or more selected from MgO, CaO, SrO, BaO, and
[0149] 0~5.0% TiO2, and
[0150] The value of Y is 19.5 or less.
[0151] Composition Example 1 is preferred because it is easy to obtain glass with high strength and good radio wave transmittance through chemical strengthening. In addition, the glass of Composition Example 1 has a small dielectric constant and a small dielectric loss tangent, so it can simultaneously suppress the absorption and reflection of radio waves and easily transmit radio waves.
[0152] (Composition Example 2)
[0153] A glass comprising:
[0154] 50.0%~75.0% SiO2,
[0155] 7.5% to 25.0% Al2O3,
[0156] 0~25.0% B2O3,
[0157] 6.5% to 20.0% Li2O,
[0158] 1.5% to 10.0% Na2O,
[0159] 0~4.0% K2O,
[0160] 1.0% to 20.0% MgO,
[0161] 1.0% to 20.0% in total of one or more selected from MgO, CaO, SrO, BaO, and
[0162] 0~5.0% TiO2, and
[0163] The value of X is 30.0 or more, and the value of Y is 19.5 or less.
[0164] Composition Example 2 is preferred because it is easy to obtain glass having high strength by chemical strengthening and good radio wave transmittance. The glass of Composition Example 2 has a large value of X and is therefore easy to become glass with higher strength.
[0165] (Composition Example 3)
[0166] A glass comprising:
[0167] 55.0%~75.0% SiO2,
[0168] 9.1%~25.0% Al2O3,
[0169] 0~14.0% B2O3,
[0170] 7.5% to 12.5% Li2O,
[0171] 3.6% to 10.0% Na2O,
[0172] 0~2.0% K2O,
[0173] 0 to 13.0% in total of one or more selected from MgO, CaO, SrO, BaO,
[0174] and 0~8.0% ZnO,
[0175] The value of X is 25.0 or more, and the value of Z is 22.0 or less.
[0176] Composition Example 3 is preferred because it is easy to obtain glass with high strength by chemical strengthening, a smaller dielectric loss tangent, and good radio wave transmittance.
[0177] (Composition Example 4)
[0178] A glass comprising:
[0179] 50.0%~75.0% SiO2,
[0180] 9.0%~25.0% Al2O3,
[0181] 0~20.0% B2O3,
[0182] 6.5% to 14.5% Li2O,
[0183] 2.5% to 10.0% Na2O,
[0184] 0~4.0% K2O,
[0185] A total of 0 to 20.0% of one or more selected from MgO, CaO, SrO, BaO, and 0 to 3.0% of TiO2,
[0186] The value of X is 35.0 or more, and the total value of Y and Z is 35.0 or less.
[0187] Composition Example 4 is preferred because it is easy to obtain glass with high strength by chemical strengthening, smaller relative dielectric constant and dielectric loss tangent, and good radio wave transmittance.
[0188] The relative dielectric constant of the present glass at 20°C and 10 GHz is preferably 7.0 or less, more preferably 6.5 or less, and further preferably 6.0 or less. The small relative dielectric constant can suppress the radio wave loss caused by reflection at the glass surface, so the radio wave transmittance tends to become good. The lower limit of the above relative dielectric constant is not particularly limited, and is usually 4.0 or more.
[0189] The dielectric loss tangent (tanδ) of the present glass at 20°C and 10GHz is preferably 0.015 or less, more preferably 0.012 or less, and further preferably 0.01 or less. By making the dielectric loss tangent small, the loss of radio waves when passing through the interior of the glass can be suppressed, so the radio wave transmittance tends to become good. The lower limit of the dielectric loss tangent is not particularly limited, and is usually 0.001 or more.
[0190] It should be noted that by making the values of the relative dielectric constant and the dielectric loss tangent at 20°C and 10 GHz close to the values of the relative dielectric constant and the dielectric loss tangent at higher frequencies, the frequency dependence (dielectric dispersion) is reduced, the frequency characteristics of the dielectric characteristics are not easy to change, and even when the frequency of use is different, the design changes are small, so it is preferred.
[0191] The relative permittivity and dielectric loss tangent can be adjusted according to the composition of the glass.
[0192] Since the alkali content in the glass composition is appropriately adjusted, the relative dielectric constant and dielectric loss tangent at 10 GHz are small. Generally, in the frequency range of about 10 GHz to about 40 GHz, the relative dielectric constant and dielectric loss tangent of glass have low frequency dependence, so the present glass with excellent dielectric properties at 10 GHz has excellent radio wave transmittance even in the 28 GHz, 35 GHz and other frequency bands used in 5G.
[0193] In addition, the relative dielectric constant and the dielectric loss tangent can be measured according to the method specified in JIS R1641 (2007) using a cavity resonator and a vector network analyzer.
[0194] The β-OH value is a value used as an indicator of the water content of glass. It is obtained by measuring the absorbance of light with a wavelength of 2.75 μm to 2.95 μm and taking the maximum value β max The value obtained by dividing by the thickness of the glass (mm).
[0195] By setting the β-OH value to 0.8 mm -1 The β-OH value is more preferably 0.6 mm. -1 Below, more preferably 0.5 mm-1 Below, more preferably 0.4 mm -1 the following.
[0196] On the other hand, by setting the β-OH value to 0.05 mm -1 The above method is preferred because it does not require melting in an extremely dry atmosphere and does not require extreme reduction of the water content in the raw materials, and can improve the productivity and bubble quality of the glass. The β-OH value is more preferably 0.1 mm -1 More preferably, 0.2 mm -1 above.
[0197] The β-OH value can be adjusted by the composition of the glass, the heat source during melting, the melting time, and the raw materials.
[0198] In the present glass, the surface compressive stress value CS0(Na) when chemically strengthened by immersion in 100% sodium nitrate salt at 450°C for 1 hour is preferably 230 MPa or more, more preferably 250 MPa or more, further preferably 300 MPa or more, further preferably 350 MPa or more, and particularly preferably 400 MPa or more. By setting the CS0(Na) value to be 230 MPa or more, it is easy to introduce sufficient compressive stress when chemically strengthening the present glass, and it is easy to obtain excellent strength. In addition, by setting the CS0(Na) value to be large to a certain extent, the compressive stress value CS0 at a depth of 50 μm from the surface is 50 When the value of CS0(Na) is too large, a large tensile stress is generated inside the chemically strengthened glass, which may cause fracture. Therefore, the value of CS0(Na) is preferably 800 MPa or less, and more preferably 700 MPa or less.
[0199] The fracture toughness value of the present glass is preferably 0.70 MPa·m 1 / 2 More preferably, 0.75 MPa·m 1 / 2 More preferably, 0.80 MPa·m 1 / 2 Above, particularly preferably 0.83 MPa·m 1 / 2 In addition, the fracture toughness value is usually 2.0MPa·m 1 / 2 Below, typically 1.5 MPa·m 1 / 2 Due to the high fracture toughness value, even if a large surface compressive stress is introduced into the glass by chemical strengthening, it is not easy to cause violent fracture.
[0200] The fracture toughness value can be measured using, for example, the DCDC method (Acta metall. mater. Vol. 43, pp. 3453-3458, 1995).
[0201] In order to make the glass less breakable, the Young's modulus of the present glass is preferably 80 GPa or more, more preferably 82 GPa or more, further preferably 84 GPa or more, and particularly preferably 85 GPa or more. There is no particular restriction on the upper limit of the Young's modulus, but a glass with a high Young's modulus sometimes has reduced acid resistance, so the Young's modulus is, for example, preferably 110 GPa or less, more preferably 100 GPa or less, and further preferably 90 GPa or less. The Young's modulus can be measured, for example, by an ultrasonic pulse method.
[0202] From the viewpoint of reducing the warpage after chemical strengthening, the average linear thermal expansion coefficient (thermal expansion coefficient) of the present glass at 50°C to 350°C is preferably 95×10 -7 / °C or less, more preferably 90×10 -7 / °C or less, more preferably 88×10 -7 / ℃ or less, particularly preferably 86×10 -7 / ℃ or less, the most preferred is 84×10 -7 There is no particular lower limit on the thermal expansion coefficient, but glass with a small thermal expansion coefficient is sometimes difficult to melt. Therefore, the average linear thermal expansion coefficient (thermal expansion coefficient) of the present glass at 50°C to 350°C is preferably, for example, 60×10 -7 / °C or more, more preferably 70×10 -7 / ℃ or more, more preferably 74×10 -7 / ℃ or more, more preferably 76×10 -7 / ℃ or above.
[0203] From the viewpoint of reducing warpage after chemical strengthening, the glass transition temperature (Tg) is preferably 500° C. or higher, more preferably 520° C. or higher, and further preferably 540° C. or higher. From the viewpoint of facilitating float forming, Tg is preferably 750° C. or lower, more preferably 700° C. or lower, further preferably 650° C. or lower, particularly preferably 600° C. or lower, and most preferably 580° C. or lower.
[0204] Viscosity reaches 10 2 The temperature (T2) at dPa·s is preferably 1750°C or less, more preferably 1700°C or less, further preferably 1675°C or less, and particularly preferably 1650°C or less. The temperature (T2) is a temperature that serves as a reference for the melting temperature of the glass. The lower T2 is, the easier it is to manufacture the glass. There is no particular restriction on the lower limit of T2, but a glass with a low T2 tends to have an excessively low glass transition temperature. Therefore, T2 is preferably 1400°C or more, and more preferably 1450°C or more, for example.
[0205] In addition, the viscosity reaches 10 4The temperature (T4) at dPa·s is preferably 1350°C or less, more preferably 1300°C or less, further preferably 1250°C or less, and particularly preferably 1150°C or less. The temperature (T4) is a temperature that serves as a reference for the temperature at which the glass is formed into a plate shape, and a glass with a high T4 tends to increase the load on the forming equipment. There is no particular restriction on the lower limit of T4, but a glass with a low T4 tends to have an excessively low glass transition temperature, so T4 is, for example, preferably 900°C or more, more preferably 950°C or more, and further preferably 1000°C or more.
[0206] When the devitrification temperature of the glass is 4 The temperature at dPa·s (T4) is preferably 120°C or lower, because devitrification is less likely to occur during the float process. The devitrification temperature is more preferably 100°C or lower than T4, further preferably 50°C or lower than T4, and particularly preferably lower than T4.
[0207] The softening point of the present glass is preferably below 850°C, more preferably below 820°C, and further preferably below 790°C. This is because the lower the softening point of the glass, the lower the heat treatment temperature in the bending forming, the less energy is consumed, and the load on the equipment is also reduced. From the viewpoint of lowering the bending forming temperature, the lower the softening point, the more preferred, but the softening point of ordinary glass is above 700°C. Glass with too low a softening point has a tendency to easily relax the stress introduced during the chemical strengthening treatment and to easily become low in strength, so the softening point is preferably above 700°C. The softening point is more preferably above 720°C, and further preferably above 740°C. The softening point can be measured by the fiber elongation method described in JIS R3103-1:2001.
[0208] In the present glass, it is preferred that the crystallization peak temperature measured by the following measurement method is higher than (softening point - 100° C.) More preferably, no crystallization peak is observed.
[0209] Specifically, about 70 mg of glass was pulverized and ground using an agate mortar, and the temperature was measured from room temperature to 1000° C. using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min.
[0210] When the present glass is in the form of a plate (glass plate), from the viewpoint of improving the effect of chemical strengthening, the plate thickness (t) is, for example, 2 mm or less, preferably 1.5 mm or less, more preferably 1 mm or less, further preferably 0.9 mm or less, particularly preferably 0.8 mm or less, and most preferably 0.7 mm or less. In addition, from the viewpoint of obtaining a sufficient effect of improving strength through chemical strengthening treatment, the plate thickness is, for example, preferably 0.1 mm or more, more preferably 0.2 mm or more, further preferably 0.3 mm or more, further preferably 0.35 mm or more, particularly preferably 0.4 mm or more, and further particularly preferably 0.5 mm or more.
[0211] The shape of the present glass may be a shape other than a plate shape depending on the applicable product, application, etc. In addition, the glass plate may also have a rim shape with different peripheral thicknesses, etc. In addition, the shape of the glass plate is not limited to this, for example, the two main surfaces may not be parallel to each other. In addition, all or a part of one or both of the two main surfaces may be a curved surface. More specifically, the glass plate may be, for example, a flat glass plate without warping, and may also be a curved glass plate with a curved surface.
[0212] The glass of the embodiment of the present invention can be manufactured by a common method. For example, the raw materials of each component of the glass are mixed and heated and melted in a glass melting furnace. Then, the glass is homogenized by a known method, formed into a desired shape such as a glass plate, and slowly cooled.
[0213] As the forming method of the glass sheet, for example, the float process, the press process, the fusion process and the down-draw process can be cited. The float process suitable for mass production is particularly preferred. In addition, continuous forming methods other than the float process, such as the fusion process and the down-draw process, are also preferred.
[0214] Then, the formed glass is ground and polished as needed to form a glass substrate. It should be noted that when the glass substrate is cut into a predetermined shape and size or the glass substrate is chamfered, if the cutting and chamfering of the glass substrate are performed before the chemical strengthening treatment described later, a compressive stress layer is also formed on the end face by the subsequent chemical strengthening treatment, which is preferred.
[0215] <Glass-ceramic>
[0216] The glass-ceramics according to the embodiment of the present invention (hereinafter also referred to as “the present glass-ceramics”) is glass-ceramics having the glass composition of the present glass described above.
[0217] The present glass-ceramics preferably contains at least one selected from lithium silicate crystals, lithium aluminosilicate crystals or lithium phosphate crystals, magnesium aluminosilicate crystals, magnesium silicate crystals and silicate crystals. As lithium silicate crystals, lithium metasilicate crystals are more preferred. As lithium aluminosilicate crystals, preferably one or more selected from petalite crystals or β-spodumene crystals, α-eucryptite and β-eucryptite. As lithium phosphate crystals, preferably lithium orthophosphate crystals.
[0218] In order to improve transparency, glass-ceramics containing lithium metasilicate crystals is more preferred.
[0219] Glass-ceramics is obtained by heating and crystallizing amorphous glass having the same composition as the present glass. The glass composition of glass-ceramics is the same as that of amorphous glass.
[0220] The visible light transmittance of microcrystalline glass (including the total visible light transmittance of diffused transmitted light) is preferably 85% or more when the thickness is 0.7 mm, so that the screen of the display can be easily seen when used as a protective glass for a portable display. The visible light transmittance is more preferably 88% or more, and even more preferably 90% or more. The higher the visible light transmittance, the more preferred, but it is usually below 93%. It should be noted that the visible light transmittance of ordinary amorphous glass is about 90% or more.
[0221] When the thickness of the glass-ceramics is not 0.7 mm, the visible light transmittance at 0.7 mm can be calculated from the measured transmittance using the Lambert-Beer law.
[0222] When the total visible light transmittance of the present glass with a plate thickness of t [mm] is 100 × T [%] and the surface reflectance of one surface is 100 × R [%], by citing the Lambert-Beer law, using the constant α, we have T = (1-R) 2 ×exp(-αt).
[0223] Here, if α is represented by R, T, and t, and t = 0.7 mm, then R does not change with the thickness of the plate, so the total visible light transmittance T of the total light with a thickness of 0.7 mm is 0.7 You can use T 0.7 =100×T 0.7 / t / (1-R)^(1.4 / t-2)[%] calculation. Where X^Y represents X Y .
[0224] The surface reflectance can be obtained by calculation based on the refractive index or can be actually measured. In addition, in the case of glass with a plate thickness t greater than 0.7 mm, the plate thickness can be adjusted to 0.7 mm by grinding, etching, etc., and the visible light transmittance can be actually measured.
[0225] In addition, the haze value is preferably 1.0% or less, more preferably 0.4% or less, further preferably 0.3% or less, particularly preferably 0.2% or less, and most preferably 0.15% or less when the thickness is 0.7 mm. The smaller the haze value, the better. However, when the crystallization rate is reduced or the crystal grain size is reduced in order to reduce the haze value, the mechanical strength is reduced. In order to improve the mechanical strength, the haze value when the thickness is 0.7 mm is preferably 0.02% or more, more preferably 0.03% or more. The haze value is a value measured according to JIS K7136 (2000).
[0226] It should be noted that, when the total visible light transmittance of the microcrystalline glass with a plate thickness of t [mm] is 100×T [%] and the haze value is 100×H [%], by citing the Lambert-Beer law and using the above constant α, it can be expressed as:
[0227] dH / dt∝exp(-αt)×(1-H).
[0228] That is, it is considered that the haze value increases in proportion to the internal linear transmittance as the plate thickness increases, so the haze value H in the case of 0.7 mm is 0.7 It is obtained by the following formula. Where “X^Y” means “X Y ”.
[0229] H 0.7 =100×[1-(1-H)^{((1-R) 2 -T 0.7 ) / ((1-R) 2 -T)}][%]
[0230] In the case of glass having a plate thickness t greater than 0.7 mm, the plate thickness may be adjusted to 0.7 mm by grinding, etching, etc., and the haze value may be actually measured.
[0231] When the reinforced glass ceramics is used as the protective glass of a portable display, it preferably has a texture and a high-grade feel different from plastic. Therefore, the refractive index of the glass ceramics is preferably 1.52 or more at a wavelength of 590 nm, more preferably 1.55 or more, and further preferably 1.57 or more.
[0232] In order to improve mechanical strength, the crystallization rate of microcrystalline glass is preferably 5% or more, more preferably 10% or more, further preferably 15% or more, and particularly preferably 20% or more. In order to improve transparency, the crystallization rate of microcrystalline glass is preferably 70% or less, more preferably 60% or less, and particularly preferably 50% or less. A low crystallization rate is also excellent in terms of being easy to bend and shape by heating.
[0233] The crystallinity ratio can be calculated from the X-ray diffraction intensity by the Riedbold method, which is described in the Crystal Analysis Handbook edited by the Crystal Analysis Handbook Editorial Committee of the Crystallographic Society of Japan (Kyoritsu Publishing, 1999, pp. 492-499).
[0234] The average particle size of the precipitated crystals of the microcrystalline glass is preferably 80 nm or less, more preferably 60 nm or less, further preferably 50 nm or less, particularly preferably 40 nm or less, and most preferably 30 nm or less. The average particle size of the precipitated crystals can be obtained from a transmission electron microscope (TEM) image. The average particle size of the precipitated crystals can be inferred from a scanning electron microscope (SEM) image.
[0235] The average thermal expansion coefficient of the glass-ceramics at 50°C to 350°C is preferably 90×10 -7 / °C or more, more preferably 100×10 -7 / °C or more, more preferably 110×10 -7 / ℃ or above, particularly preferably 120×10 -7 / ℃ or above, most preferably 130×10 -7 / ℃ or above.
[0236] When the thermal expansion coefficient is too large, cracks may occur during the chemical strengthening process due to the difference in thermal expansion rate. Therefore, the average thermal expansion coefficient at 50°C to 350°C is preferably 160×10 -7 ℃ or less, more preferably 150×10 -7 ℃ or less, more preferably 140×10 -7 below ℃.
[0237] Since glass-ceramics contains crystals, it has a high hardness. Therefore, it is not easy to be damaged and has excellent wear resistance. In order to increase the wear resistance, the Vickers hardness is preferably 600 or more, more preferably 700 or more, further preferably 730 or more, particularly preferably 750 or more, and most preferably 780 or more.
[0238] When the hardness is too high, processing becomes difficult, and therefore the Vickers hardness of the microcrystalline glass is preferably 1100 or less, more preferably 1050 or less, and further preferably 1000 or less.
[0239] In order to suppress the warping caused by strengthening during chemical strengthening, the Young's modulus of microcrystalline glass is preferably more than 85GPa, more preferably more than 90GPa, more preferably more than 95GPa, and particularly preferably more than 100GPa. Microcrystalline glass is sometimes used after grinding. In order to easily grind, the Young's modulus is preferably less than 130GPa, more preferably less than 125GPa, and more preferably less than 120GPa.
[0240] The fracture toughness value of the glass-ceramics is preferably 0.8 MPa·m 1 / 2 More preferably, 0.85 MPa·m 1 / 2 More preferably, 0.9 MPa·m 1 / 2 When the fracture toughness value is the above value or more, it is preferable because fragments are less likely to scatter when the steel sheet is broken when chemical strengthening is performed.
[0241] The present glass-ceramic has the same glass composition as the above-mentioned present glass. That is, the present glass-ceramic is obtained by heating and crystallizing amorphous glass having the same glass composition as the present glass. By making the present glass-ceramic have the same glass composition as the present glass, excellent strength can be obtained by chemical strengthening in the same manner as the present glass, and excellent radio wave transmittance can be obtained.
[0242] <Chemically strengthened glass>
[0243] The chemically strengthened glass (hereinafter also referred to as "the present chemically strengthened glass") of an embodiment of the present invention is obtained by chemically strengthening the present glass or the present glass-ceramics described above. That is, the basic composition of the present chemically strengthened glass is the same as the glass composition of the present glass described above, and the preferred composition range is also the same. In the chemically strengthened glass, except for the case where an extreme ion exchange treatment is performed, the glass composition at a depth of 1 / 2 of the plate thickness t is the same as the basic composition of the chemically strengthened glass. In addition, the average composition of the present chemically strengthened glass is the same as the composition of the present glass or the present glass-ceramics. Here, the average composition refers to the composition obtained by analyzing a sample after finely crushing a glass sample after heat treatment from a glass state.
[0244] The surface compressive stress value CS0 of the chemically strengthened glass is preferably 300 MPa or more, more preferably 350 MPa or more, further preferably 400 MPa or more, further preferably 450 MPa or more, and particularly preferably 500 MPa or more. By setting the surface compressive stress value CS0 to 300 MPa or more, it is easy to obtain excellent strength. In addition, the compressive stress value CS0 at a depth of 50 μm from the surface is 50 It is also easy to enlarge, so it is preferred.
[0245] The greater the surface compressive stress value CS0, the higher the strength. However, when the surface compressive stress value CS0 is too large, a large tensile stress is generated inside the chemically strengthened glass, which may cause fracture. From this point of view, the surface compressive stress value CS0 is preferably 1000 MPa or less, and more preferably 800 MPa or less.
[0246] In the stress distribution of the chemically strengthened glass, the compressive stress value CS at a depth of 50 μm from the surface is 50 It is preferably 75 MPa or more, more preferably 90 MPa or more, further preferably 100 MPa or more, and particularly preferably 125 MPa or more. 50 The chemically strengthened glass is not easily broken when it is damaged by falling or the like.
[0247] The internal tensile stress value CT of the chemically strengthened glass is preferably 80 MPa or less, more preferably 75 MPa or less. The smaller the CT, the less likely it is to break. The internal tensile stress value CT is preferably 50 MPa or more, more preferably 60 MPa or more, and further preferably 65 MPa or more. When the CT is above the above value, the compressive stress near the surface increases and the strength increases.
[0248] When the depth DOL of the compressive stress layer of the present chemically strengthened glass is too large relative to the thickness t (μm), it leads to an increase in CT, so DOL is preferably 0.25t or less, more preferably 0.2t or less, further preferably 0.19t or less, and further preferably 0.18t or less. In addition, from the viewpoint of improving strength, DOL is preferably 0.06t or more, more preferably 0.08t or more, further preferably 0.10t or more, and particularly preferably 0.12t or more. Specifically, for example, when the plate thickness t is 700μm (0.7mm), DOL is preferably 140μm or less, more preferably 133μm or less. In addition, DOL is preferably 70μm or more, more preferably 80μm or more, and further preferably 90μm or more. It should be noted that the preferred plate thickness (t) and preferred shape of the present chemically strengthened glass are the same as the preferred plate thickness (t) and shape of the present glass described above.
[0249] The chemically strengthened glass can be produced by subjecting the obtained glass plate to a chemical strengthening treatment, and then washing and drying the plate.
[0250] The chemical strengthening treatment can be performed by a known method. In the chemical strengthening treatment, the glass sheet is contacted with a melt of a metal salt (e.g., potassium nitrate) containing a metal ion with a large ionic radius (typically a K ion) by immersion or the like. Thus, the metal ions with a small ionic radius (typically a Na ion or a Li ion) in the glass sheet are replaced with metal ions with a large ionic radius (typically, K ions for Na ions and Na ions for Li ions).
[0251] The chemical strengthening treatment (ion exchange treatment) can be performed, for example, by immersing the glass plate in a molten salt such as potassium nitrate heated to 360° C. to 600° C. for 0.1 to 500 hours. It should be noted that the heating temperature of the molten salt is preferably 375° C. to 500° C., and the immersion time of the glass plate in the molten salt is preferably 0.3 to 200 hours.
[0252] As molten salts for chemical strengthening treatment, for example, nitrates, sulfates, carbonates, chlorides, etc. can be listed. Among them, as nitrates, for example, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate and silver nitrate can be listed. As sulfates, for example, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, etc. can be listed. As carbonates, for example, lithium carbonate, sodium carbonate and potassium carbonate can be listed. As chlorides, for example, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, etc. can be listed. These molten salts can be used alone or in combination.
[0253] In the present invention, the treatment conditions of the chemical strengthening treatment can be appropriately selected in consideration of the properties and composition of the glass, the type of molten salt, and the chemical strengthening properties such as the desired surface compressive stress and the depth of the compressive stress layer of the final chemically strengthened glass.
[0254] In addition, in the present invention, chemical strengthening treatment may be performed only once or multiple chemical strengthening treatments may be performed under two or more different conditions (multi-step strengthening). Here, for example, as the first step of chemical strengthening treatment, chemical strengthening treatment is performed under the condition that DOL is large and CS is relatively small. Then, as the second step of chemical strengthening treatment, when chemical strengthening treatment is performed under the condition that DOL is small and CS is relatively high, the CS of the outermost surface of the chemically strengthened glass can be increased while suppressing the internal tensile stress area (St), and the internal tensile stress (CT) can be suppressed to a low level.
[0255] The present glass is particularly useful as a protective glass used in mobile devices such as mobile phones, smart phones, portable information terminals (PDAs), and tablet terminals. In addition, it is also useful as protective glass for display devices such as televisions (TVs), personal computers (PCs), and touch panels that are not intended to be carried, building materials such as elevator walls, walls of buildings such as houses or buildings (full-screen displays), window glass, desktops, interiors of cars or airplanes, etc., or protective glass thereof, and in housings having non-plate-shaped curved surfaces by bending or forming.
[0256] Example
[0257] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited thereto.
[0258] The glass raw materials were prepared to have the compositions in terms of molar percentage based on oxides in Tables 1 to 6, and were weighed so that the glass weight reached 400 g. Next, the mixed raw materials were placed in a platinum crucible and melted in an electric furnace at 1500° C. to 1700° C. for about 3 hours, and then degassed and homogenized. It should be noted that in the table, Mg+Ca+Sr+Ba means [MgO]+[CaO]+[SrO]+[BaO].
[0259] The obtained molten glass was poured into a metal mold, kept at a temperature about 50°C higher than the glass transition temperature for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The obtained glass block was cut and ground, and finally both sides were mirror-polished to obtain a glass plate with a thickness of 600μm. Examples 1 to 50 are examples of the present glass, and Examples 51 to 53 are comparative examples.
[0260] The relative dielectric constant ε' and dielectric loss tangent tanδ of each glass were measured at 20°C and 10 GHz. The measurements were performed using a cavity resonator and a vector network analyzer according to the method specified in JIS R1641 (2007). The measurement frequency was set to the resonant frequency of air in the cavity resonator at 20°C and 10 GHz. The results are shown in Tables 1 to 6.
[0261] In addition, each glass was chemically strengthened by immersing it in 100% sodium nitrate at 450°C for 1 hour. The surface compressive stress value CS0(Na) and the compressive stress depth DOL after chemical strengthening were measured using a scattered light photoelastic stress meter SLP-1000 manufactured by Orihara Seisakusho Co., Ltd. The results are shown in Tables 1 to 6. In the table, blank columns indicate that no measurement was performed.
[0262] For the glasses of Examples 1 to 50, the relationship between the value of parameter X and the surface compressive stress value CS0(Na) after chemical strengthening is shown in FIG. Figure 1 In. By Figure 1 It can be confirmed that the larger the parameter X is, the larger the CS0(Na) is.
[0263] For the glasses of Examples 1 to 50, the relationship between the value of parameter Y and the relative dielectric constant at 20°C and 10 GHz is shown in Figure 2 In. By Figure 2 It can be confirmed that the smaller the parameter Y is, the smaller the relative dielectric constant at 20° C. and 10 GHz is.
[0264] The correlation between the value of parameter Z and the dielectric loss tangent at 20°C and 10 GHz for the glasses of Examples 1 to 50 is shown in FIG. Figure 3 In. By Figure 3It can be confirmed that the smaller the parameter Z is, the smaller the dielectric loss tangent at 20° C. and 10 GHz is.
[0265]
[0266]
[0267]
[0268]
[0269]
[0270] Table 6
[0271] (mol%) Example 51 Example 52 Example 53 <![CDATA[SiO2]]> 67.2 56.1 67.7 <![CDATA[Al2O3]]> 13.1 17.2 15.4 <![CDATA[B2O3]]> 3.6 0.0 0.0 <![CDATA[P2O5]]> 0.0 7.0 0.0 MgO 2.3 2.7 0.0 CaO 0.0 0.0 0.0 SrO 0.0 0.0 0.0 BaO 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.0 0.2 0.0 <![CDATA[Y2O3]]> 0.0 0.0 0.0 <![CDATA[Li2O]]> 0.0 0.0 6.2 <![CDATA[Na2O]]> 13.7 16.8 10.7 <![CDATA[K2O]]> 0.1 0.0 0.0 total 100.0 100.0 100.0 Mg+Ca+Sr+Ba 2.3 2.7 0.0 X 14.2 20.7 31.0 Y 22.1 26.8 23.7 Z 83.3 118.8 76.6 Y+Z 105.4 145.6 100.3 <![CDATA[CS0(Na)[MPa]]]> – – 125 DOL[μm] – – 129 ε'@10GHz 6.8 7.6 6.9 tanδ@10GHz 0.0250 0.0193 0.0075
[0272] The surface compressive stress values of the glasses of Examples 1 to 50 as working examples after chemical strengthening were greater than 230 MPa, and excellent strength was obtained by chemical strengthening.
[0273] In addition, it was confirmed that the glasses of Examples 1 to 50 had good relative dielectric constant ε' and dielectric loss tangent tanδ at 20°C and 10 GHz and had excellent radio wave transmittance.
[0274] On the other hand, the glasses of Examples 51 and 52 as comparative examples do not contain lithium ions, and it is difficult to achieve high strength by chemical strengthening using sodium salt. In addition, the relative dielectric constant and tanδ of the glasses of Examples 51 and 52 are large, and cannot be said to have good radio wave transmittance. In addition, although the glass of Example 53 has a small tanδ, the surface compressive stress value during chemical strengthening is insufficient, and as a result, it is impossible to achieve both strength and radio wave transmittance.
[0275] Although the present invention is described in detail and with reference to specific embodiments, various changes and modifications can be made without departing from the spirit and scope of the present invention, which is obvious to those skilled in the art. This application is based on Japanese patent application (Japanese patent application 2020-115920) filed on July 3, 2020, the contents of which are incorporated herein by reference.
Claims
1. A glass comprising, in terms of molar percentage based on oxides: 50.0%~75.0% SiO2, 7.5% to 25.0% Al2O3, 5.0% to 25.0% B2O3, 6.5% to 20.0% Li2O, 1.5% to 6.0% Na2O, 0~4.0% K2O, 1.0% to 20.0% MgO, 1.0% to 20.0% in total of one or more selected from MgO, CaO, SrO, BaO, and 0~5.0% TiO2, Does not contain Gd2O3, The thermal expansion coefficient of 50℃~350℃ is 60×10 -7 / ℃ or above, and The value of Y calculated based on the following formula using the contents of MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], and [K2O] of each component is 17.5 or less, Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O]).
2. The glass according to claim 1, wherein: The content of each component of Al2O3, MgO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [Al2O3], [MgO], [Li2O], [Na2O], [K2O], and the value of X calculated based on the following formula is 30.0 or more, X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O]).
3. A glass, wherein: The glass contains, in mole percentage based on oxides: 55.0%~75.0% SiO2, 9.1%~25.0% Al2O3, 0~14.0% B2O3, 7.5% to 12.5% Li2O, 3.6% to 6.0% Na2O, 0~2.0% K2O, 0 to 13.0% in total of one or more selected from MgO, CaO, SrO, and BaO, and 0 to 8.0% of ZnO, Does not contain Gd2O3, The thermal expansion coefficient of 50℃~350℃ is 60×10 -7 / ℃ or above, and Using the contents of each component of Al2O3, B2O3, MgO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [Al2O3], [B2O3], [MgO], [Li2O], [Na2O], [K2O], the value of X calculated based on the following formula is 25.0 or more, and the value of Z is 12.0 or less, The Young's modulus of the glass is 80 GPa or more, X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O]) Z=3×[Al2O3]-3×[B2O3]-2×[Li2O]+4×[Na2O].
4. A glass, wherein: The glass contains, in mole percentage based on oxides: 50.0%~75.0% SiO2, 9.0%~25.0% Al2O3, 8.0% to 20.0% B2O3, 6.5% to 14.5% Li2O, 2.5% to 6.0% Na2O, 0~4.0% K2O, A total of 0 to 20.0% of one or more selected from MgO, CaO, SrO, BaO, and 0 to 3.0% of TiO2, Does not contain Gd2O3, The thermal expansion coefficient of 50℃~350℃ is 60×10 -7 / ℃ or above, and Using the contents of each component of Al2O3, B2O3, MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O in terms of oxide-based molar percentage [Al2O3], [B2O3], [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], and [K2O], the value of X calculated based on the following formula is 35.0 or more, and the total value of the value of Y and the value of Z is 28.0 or less, X=3×[Al2O3]+[MgO]+[Li2O]-2×([Na2O]+[K2O]) Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O]) Z=3×[Al2O3]-3×[B2O3]-2×[Li2O]+4×[Na2O].
5. The glass according to any one of claims 1 to 4, wherein The glass has a plate thickness (t) of 100 μm or more and 2000 μm or less.
6. A chemically strengthened glass, wherein: The basic composition of the chemically strengthened glass comprises, in terms of molar percentage based on oxides: 50.0%~75.0% SiO2, 5.0% to 25.0% B2O3, 7.5% to 25.0% Al2O3, 6.5% to 20.0% Li2O, 1.5% to 6.0% Na2O, 0~4.0% K2O, 1.0% to 20.0% MgO, 1.0% to 20.0% in total of one or more selected from MgO, CaO, SrO, BaO, and 0~5.0% TiO2, Does not contain Gd2O3, The thermal expansion coefficient of 50℃~350℃ is 60×10 -7 / ℃ or above, and The value of Y calculated based on the following formula using the contents of MgO, CaO, SrO, BaO, Li2O, Na2O, and K2O in terms of molar percentage on an oxide basis [MgO], [CaO], [SrO], [BaO], [Li2O], [Na2O], and [K2O] of each component is 17.5 or less, Y=1.2×([MgO]+[CaO]+[SrO]+[BaO])+1.6×([Li2O]+[Na2O]+[K2O]).
7. The chemically strengthened glass according to claim 6, wherein: The surface compressive stress value CS0 of the chemically strengthened glass is greater than or equal to 300 MPa.
8. The chemically strengthened glass according to claim 6 or 7, wherein: The compressive stress value CS at a depth of 50 μm from the glass surface of the chemically strengthened glass is 50 The pressure is 75 MPa or more, and the thickness (t) of the chemically strengthened glass is 300 μm or more.
9. The chemically strengthened glass according to any one of claims 6 to 8, wherein The chemically strengthened glass has a compressive stress layer depth DOL of 80 μm or more, and a plate thickness (t) of 350 μm or more.
10. A glass-ceramic, wherein: The glass-ceramics has the glass composition of the glass according to any one of claims 1 to 4.
Citation Information
Patent Citations
Glass with high surface strength
JP2018520082A
Low viscosity glass and manufacturing method and system
JP2019532906A
Pachinko game machine
JP2020115920A
Glass substrate, liquid crystal antenna and high-frequency device
WO2019181707A1
Method for producing tempered glass with plurality of surface stress layers and tempered glass product
CN102815860A